Policing and Minority Communities - Albrecht, James F.; Heyer, Garth den; Stanislas, Perry (Springer, 2019)
At the inception of professional policing in the 1820s, Sir Robert Peel emphasized the relevance of the role that the community should play in assessing the efficacy of the police and in setting the priorities for professional public security. After highlighting the basic mission of the police in crime and disorder control, the second of Peel’s nine principles of policing (Lee 1901) clearly delineates that “(t)he ability of the police to perform their duties is dependent upon public approval of police actions,” and continues in Principle five with the assertion that the “(p)olice seek and preserve public favor not by catering to the public opinion but by constantly demonstrating absolute impartial service to the law.” And the most noteworthy point noted was that the police “at all times, should maintain a relationship with the public that gives reality to the historic tradition that the police are the public and the public are the police.” It is obvious from the initial foundation of the law enforcement profession almost two centuries ago that the input and feedback of the public being served must be viewed as being paramount in assessing the effectiveness of police performance. Clearly the relevance of these perspectives applies to all members of the public, not only to those who have connections with the political leadership and the elite, but to all citizens, regardless of social class, ethnicity or other influential factor. More importantly, failing these vital principles will result in the loss of trust and confidence in the police, the criminal justice system, and likely the government as a whole.
Contemporary Issues and Global Perspectives